Peran Pendidikan Karakter Siswa SD Dalam Menghadapi Teknologi Abad 21 - Aulia Nur Jannah; Putri Salma N (Universitas Palangka Raya, 2024)
The progress of technological developments cannot be avoided so the role of character education is very necessary in welcoming education in the 21st century. Moreover, in 21st century education, especially for elementary school students, most schools have introduced technology. This article aims to find out and analyze more deeply the role of character education for elementary school students in facing 21st century educational technology. This research study uses qualitative data collection techniques or a descriptive approach. Where the theory and basis for discussion are obtained from the results of literature studies from several sources such as books, journals and articles. Instilling character education from school age, especially at elementary school level, is important so that it can form the character of students who are responsible, caring, have integrity and think critically in acting using technology in education.